2008
DOI: 10.1592/phco.28.6.685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Single Fixed Dose of Rasburicase 7.5 mg for the Treatment of Hyperuricemia in Adults with Cancer

Abstract: A single 7.5-mg intravenous dose of rasburicase appeared to have effects similar to those of a single 0.15-mg/kg intravenous dose for the treatment or prevention of hyperuricemia associated with tumor lysis syndrome. This low fixed dose also has the potential to reduce costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 13 publications
2
54
1
Order By: Relevance
“…11 A similar efficacy of single dose rasburicase was also observed in our case series with patients who were predominantly Chinese. Several small-scale studies [4][5][6][7][8] have also shown that a single dose of rasburicase produces a rapid uric acidlowering effect that is beneficial for patients manifesting TLS. Similarly, our case series has shown that a single 6 mg dose of rasburicase significantly lowered uric acid levels within the first 24 h of administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A similar efficacy of single dose rasburicase was also observed in our case series with patients who were predominantly Chinese. Several small-scale studies [4][5][6][7][8] have also shown that a single dose of rasburicase produces a rapid uric acidlowering effect that is beneficial for patients manifesting TLS. Similarly, our case series has shown that a single 6 mg dose of rasburicase significantly lowered uric acid levels within the first 24 h of administration.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, a number of studies have demonstrated the effectiveness of a single reduced dose of rasburicase for the management of TLS in adults. [4][5][6][7][8] A recently published study has shown that the mean reduction of uric acid concentrations by rasburicase is 88% after patients receive their first dose. 9 It is reasonable to believe that a single dose of rasburicase is effective for reducing uric acid, as the onset of action of rasburicase is typically within 4 h. 3 Whether Asian lymphoma patients respond equally well to a single reduced dose of rasburicase is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Rasburicase is Food and Drug Administration (FDA)approved for the prevention and management of hyperuricemia in adults and children with cancer at a dose of 0.20 mg/kg IV over 30 min as a single daily dose for up to 5 days (Elitek ® package insert). Studies have examined the efficacy and different dosing schedules for rasburicase (Campara, Shord, and Haaf, 2009;Hummel et al, 2008a;Hutcherson et al, 2006;Kennedy and Ajiboye, 2010;Lee et al, 2003;Liu, Sims-Mccallum, and Schiffer, 2005;Malaguarnera et al, 2009;McDonell et al, 2006;Reeves and Bestul, 2008;Trifilio et al, 2006). Other benefits to rasburicase include lack of drug interactions and no requirements for dose adjustments in renal dysfunction (Kennedy and Ajiboye, 2010).…”
Section: Hyperuricemiamentioning
confidence: 99%
“…An expert panel convened in 2010, sponsored by the manufacturer of rasburicase (SanofiAventis), recommended the prophylactic use of rasburicase in adults with a high-risk malignancy, with other patients receiving rasburicase after chemotherapy in the setting of elevated uric acid levels (51). Several cohort studies have demonstrated persistently suppressed serum uric acid concentrations with one-time dosing; a dose of 0.15 mg/kg seems to be a clinically reasonable and cost-effective approach (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). Repeat dosing may be needed if uric acid remains at or increases above 8.0 mg/dl after the initial dose (75).…”
Section: Recombinant Urate Oxidasementioning
confidence: 99%